A single-step method for synthesis of CuInS2 nanostructures using cyclic microwave irradiation - Chumha N. (2017)
© 2016 Elsevier Ltd and Techna Group S.r.l. Pure and well-crystalline CuInS 2 nanostructures were successfully synthesized via a cyclic microwave irradiation method at low microwave power using cupric chloride dihydrate (CuCl 2 ·2H 2 O), indium chloride tetrahydrate (InCl 3 ·4H 2 O) and thioacetamide as starting reagents. The effects of processing cycles (2–75 cycles) and microwave heating powers (180–600 W) on purity, crystallinity, particle size and morphology of the synthesized products were investigated. The synthesized products were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and UV–vis spectroscopy. Increasing processing cycles and microwave heating power improved the purity and crystallinity of the synthesized products. Using the microwave powers of 450 and 600 W with 75 cycles, pure CuInS 2 nanocrystallites were obtained. The CuInS 2 crystallites displayed nanoparticles in clusters with decreasing in the diameter sizes from 1.6 to 0.9 µm when the microwave power was increased from 180 to 600 W. The reaction mechanism of the CuInS 2 formation was also provided. A CuInS 2 solar cell, made from FTO/TiO 2 /CuInS 2 /CdS/Pt-FTO layers, was fabricated to explore the potential use of the CuInS 2 nanoparticles in photovoltaic devices. The photovoltaic properties of the CuInS 2 solar cell including open-circuit voltage (V oc ), short-circuit current density (J sc ) and fill factor (FF) were 281.10 mV, 0.072 mA/cm 2 and 0.47, respectively, with cell conversion efficiency (η) of 0.01% under 1.5 AM illumination.